Um mergulho em um mar de documentos: reflexões sobre o processo de nomeação dos Krenyê no Judiciário - MADEIRO, Joiza Maria de Arruda (2023)
Based on Bourdieu's (2014) conception that the State is one of the entities in the social space that is most skilled at naming and classifying, I described the process of naming the Krenyê people and recognizing their right to land in the brazilian State, as well as the role that spokespersons for these people and state agents played in this process. To do so, I analyzed documents contained in a Public Civil Action proposed to the Federal Court by the Federal Public Ministry so that the Union and Funai allocate land for this people. The purpose of this work is to understand how the Krenyê, formerly known generically as Timbira, needed to be named as a specific people - the Krenyê - in order to conquer their lands.